Factors That Explain Academic Dishonesty Among University Students in Thailand. Issue 2 (17th February 2017) - Thomas, Darrin
Abstract : Academic dishonesty is a problem that continues to plague universities. Few studies have examined how mind-set and individualism contribute to academic dishonesty. Using structural equation modeling, a model was developed to explain academic dishonesty, which included mind-set, individualistic learning environment, individualism, and motivation to study. A total of 207 university students in Thailand participated. The final model explained 30% of the variance in academic dishonesty. All variables in this study had a negative relationship with academic dishonesty, indicating that improvements in mind-set, learning environment, and motivation could change perceptions of academic dishonesty.